Prishvin about Stalin’s Cult of Personality: Notes of Contemporary - A. M. Podoksenov (Научный диалог)
The novelty of the study is seen in the unexplored question about Prishvin’s attitude to Stalin’s cult of personality. The evolution of the writer’s views on the role of Stalin in the establishment and development of the Soviet state is considered based on the material first introduced into scientific circulation, summarized from the 18-volume Pryshvin’s “Diary”, which became available to the reader only recently. The aim of the study is to show that as a man with a historiosophical mindset, Pryshvin is far from thinking that the cause of the cult of personality is solely Stalin’s fault because of his treachery and despotism. It is noted that the significance of Prishvin’s conclusions about the origins and causes of the Stalinist cult also lies in the fact that the writer’s conclusions largely anticipate the conclusions of many later researchers of the Soviet era. It has been established that Prishvin’s analysis of the objective and subjective factors of the emergence of Stalin’s personality cult shows the reader that before him is not only a talented artist of words, but also an extraordinary thinker with his own philosophical view on the most pressing ideological-political, economic and socio-cultural problems of his time.